A luminescent cadmium metal–organic framework for sensing of nitroaromatic explosives. Issue 1 (5th November 2014) - Zhang, Chuanqi; Sun, Libo; Yan, Yan; Li, Jiyang; Song, Xiaowei; Liu, Yunling; Liang, Zhiqiang
Abstract : A novel metal–organic framework1 was synthesized using a new rigid unsymmetrical tricarboxylate ligand p -terphenyl-3, 4′′, 5 tricarboxylate (H3 TPT). The micrometer-sized material1′ dispersed in ethanol exhibits high efficiency for the detection of PA. Abstract : A novel metal–organic framework [Cd3 (TPT)2 (DMF)2 ]·(H2 O)0.5 (1 ) has been solvothermally synthesized using a new rigid unsymmetrical tricarboxylate ligand p -terphenyl-3, 4′′, 5-tricarboxylic acid (H3 TPT). Single-crystal X-ray diffraction analysis reveals that1 possesses a three-dimensional (3D) framework with an alb-4, 8- C 2/ c topology constructed by the combination of Cd–carboxylate chains and TPT linkers. The π-electron rich ligand H3 TPT enables1 to have an excellent luminescent property. The micrometer-sized compound1′ dispersed in ethanol exhibits high efficiency detection for picric acid (PA). The high efficiency, stability and recyclability of1′ make it a potential chemosensor for nitroaromatic explosives.